Estudo exploratório da utilização de um rotor banki como turbina eólica - Poleze, Juliano (2017)
The Wind energy is currently, the most promising renewable energy and with a better cost-benefit for exploration, and it doesn t cause considerable impacts in environment. For the construction of large units of wind power has been used horizontal axis turbines, which are researched and exploited in many countries. These turbines show a good performance, but they aren t capable starting the operation with low wind speeds. Turbines like Savonius, with vertical axis, show a low efficiency, limiting their use in areas with little wind. This study has like base, the exploratory research of small-size wind turbine to be used in places with low intensity winds. For this uses up the rotor of a hydraulic Michell-Banki turbine, also known as cross-flow turbine, to function as a vertical axis turbine. The study presents the prototype of the design, the manufacturing and installation process. They are collected preliminaries data on its operation and a preliminary assessment of this type of rotor for use as wind turbine